2009
DOI: 10.3917/spub.091.0037
|View full text |Cite
|
Sign up to set email alerts
|

Perception par les patients de l'information reçue lors d'un examen complémentaire

Abstract: Medical doctors are required to provide information to their patients regarding their medical procedures according to the law on patient information enacted on March 4, 2002. The objective of this study was to assess patients' awareness and satisfaction with respect to their perception of information obtained prior to or during a medical examination. A self-descriptive patient survey was conducted at the Groupe Hospitalier of Pitié-Salpêtrière in 2005 for this purpose. Data were collected at three distinct mom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…It should be recalled that the domain of information is the one where several studies describe patients' concerns. A French survey assessing patient satisfaction with regard to information received before or during a complementary medical examination notes that 20% of the participants had not received any specific medical or paramedical information before the examination and 4% had received no information at all [29]. In other countries, 20.4% of Germans; 23.4% of Swedes, 16.7% of Swiss, 28.7% of Britishs and 25.2% of Americans were dissatisfied with the information they had received [22].…”
Section: Discussionmentioning
confidence: 99%
“…It should be recalled that the domain of information is the one where several studies describe patients' concerns. A French survey assessing patient satisfaction with regard to information received before or during a complementary medical examination notes that 20% of the participants had not received any specific medical or paramedical information before the examination and 4% had received no information at all [29]. In other countries, 20.4% of Germans; 23.4% of Swedes, 16.7% of Swiss, 28.7% of Britishs and 25.2% of Americans were dissatisfied with the information they had received [22].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the quality of the information provided to patients is a major determinant of the satisfaction with their care [11]. However, many patients are provided limited information about their hospital care [12-14], and feel that more attention should be paid to nontechnical aspects of their care [15]. In one study [13], 20% of the patients who underwent diagnostic tests reported problems with communication of the test results.…”
Section: Introductionmentioning
confidence: 99%